Good guys : how men can be better allies for women in the workplace - Smith, David 1965- (Harvard Business Review Press, 2020)
"What's missing from gender equality efforts? Men. Women are at a disadvantage in the workplace, where they deal with unequal pay, sexual harassment, lack of credit for their contributions, and more. And while organizations are looking to address these issues, too many gender-inclusion initiatives focus exclusively on how women should respond, leaving men out of the equation. Such efforts reinforce the perception that these are "women's issues" and that men--often the most powerful stakeholders in an organization--don't need to be involved. As gender-in-the-workplace experts David G. Smith and W. Brad Johnson show in this important book, men have a crucial opportunity to promote gender equality at work. Research shows that when men are deliberately engaged in gender-inclusion programs, 96 percent of women in those organizations perceive real progress in gender equality, compared with only 30 percent of women in organizations without strong male engagement. Good Guys is the first book to provide a practical, research-based guide for how to be a male ally to women in the workplace. Filled with firsthand accounts from both men and women, as well as tips for getting started, the book shows how men can partner with their female colleagues to advance women's leadership and equality by breaking ingrained gender stereotypes, overcoming unconscious biases, developing and supporting the talented women around them, and creating productive and respectful working relationships with women--especially in a post-#MeToo world"--